An assessment of mathematics teachers’ Internet self-efficacy: implications on teachers’ delivery of mathematics instruction (2011)
This study examined the mathematics teachers’ Internet self-efficacy and its possible influence on the delivery of mathematics instruction. The participants were 90 mathematics teachers selected from various schools in five local government areas of Osun State, Nigeria. The results demonstrated that to a great extent mathematics teachers have high Internet self-efficacy and that correlation exists between mathematics teachers’ age, Internet usage and Internet self-efficacy. Irrespective of gender, mathematics teachers have the same level of Internet self-efficacy. Moreover, Internet self-efficacy and usage were revealed to drastically improve the way teacher teach mathematics and conduct research. Upon these findings, it was recommended that mathematics teachers who do not know how to browse and search the Internet should consider doing so now without wasting much time. There is also the need to increase Internet usage, on the part of the mathematics teachers who just begin using the Internet. They need to do this considering the fact that increased usage leads to high Internet self-efficacy. Moreover, it is high time to close the technology gender gap which has been in existence since a long time. This can start from the mathematics teachers.